Dynamics of earnings and hourly wages in Germany - Michał Myck; Richard Ochmann; Salmai Qari (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
There is by now a lot of evidence showing a sharp increase in cross-sectional wage and earnings inequality during the 2000s in Germany. Our study is the first to decompose this cross-sectional variance into its permanent and transitory parts for years beyond 2000. Using data from the German Socio-Economic Panel on fulltime working individuals for years of 1994 to 2006, we do not find unambiguous empirical support for the frequent claims that recent increases in inequality have been driven mainly by permanent disparities. From 1994 on, permanent inequality increases continuously, peaks in 2001 but then declines in subsequent years. Interestingly the decline in the permanent fraction of inequality occurs at the time of most rapid increases in cross-sectional inequality. It seems therefore that it is primarily the temporary and not the permanent component which has driven the strong expansion of cross-sectional inequality during the 2000s in Germany.
Keywords: C23; D31; J31; 330; Variance decomposition; covariance structure models; earnings inequality; wage dynamics; Lohnstruktur; Soziale Ungleichheit; Soziale Mobilität; Schätzung; Arbeitsverhältnis; Deutschland